A37 Does The Installation of Bicycle Boulevards Improve Residents' Perceptions of The Bicycling and Walking Environment? A Panel Study. Issue 2 (June 2015) - Ma, Liang; Dill, Jennifer
Abstract: Background: The causal relationships between the built environment, perceptions and active travel remain less well understood. This study aims to evaluate the effects of the traffic-calming infrastructure, bicycle boulevards, on improving residents' perceptions of the bicycling and walking environment. Bicycle boulevard, also known as neighborhood greenway, is a low-traffic street with traffic calming devices that reduce the volume and speed of motor vehicle traffic and treatments at intersections with major streets that facilitate safe crossing. Methods: This analysis uses data from the Family Activity Study (FAS). The Family Activity Study is a longitudinal study of the effects of traffic calming infrastructure (bicycle boulevards) on behavior. The study started with 335 households living in 19 study sites (nine treatments and ten controls). Surveys were conducted at two points in time: Pre and Post. The Pre (n=491 adults) and Post (n=385) surveys are approximately two years apart, with bicycle boulevard construction occurring in between. The surveys include personal and household socio-demographics, subjective perceptions of their neighborhood environment, travel attitudes, social norms, self-efficacy towards travel behavior, and self-reported biking and walking behavior. The difference-in-differences estimator was used to evaluate whether there is significant differences between the treatment and control groups in terms of the changes of perceptions before and after the installation of the bicycle boulevard. Results: The model results indicated that three of the five interaction terms were statistically significant, suggesting that changes of perceptions of neighborhood attractiveness, changes of perceptions of walking accessibility, and changes of overall perceptions of the neighborhood environment were significantly different between treatment and control group. In particular, the perceptions of residents in treatment group increased after the treatment, while the perceptions of residents in control group decreased. Conclusions: Installation of the bicycle boulevards might help to improve the perceptions of the residents on their neighborhood environment for walking and attractiveness. This is particularly evident for the improvement of the perceptions on neighborhood attractiveness and walking accessibility. Surprisingly, this study did not find the significant effects of the bicycle boulevards on improving people's perceptions of traffic safety, which are thought to be the direct effects of a bicycle boulevard considering most of its elements are associated with traffic calming. This finding suggested that installation of the bicycle boulevards in neighborhoods might not have immediate effects on improving the perceptions of traffic safety.